Analysis of Credit Risk and its Impact on Financial Soundness - Analytical Study of the Bank of Baghdad in Iraq for the Period (2005-2019( - faisal Djihad, Djihad; Hassen Mohammed ali, Saimaa (Finance and Business Economies Review, 2021)
This research aims to study the effect of credit risk on financial soundness , The Bank of Baghdad was chosen in the city of Baghdad, which is one of the largest private commercial banks in Iraq , In addition, the bank has a presence in the Middle East and North Africa and consists of (7) partner banks (Bank of Baghdad in Iraq, Bank of Syria and the Gulf in Syria, Gulf Bank Algeria in Algeria, Jordan Kuwait Bank in Jordan, Tunis International Bank in Tunisia, Burgan Bank. In Kuwait, United Gulf Bank in Bahrain). The time period for the search was for annual data from 2005 to 2019. The research started from a problem (Is there an impact of credit risk on financial safety indicators?) Due to its great impact on the success of banking activity. In order to analyze the effect, the SPSS statistical package program was used according to the simple linear regression method, The most important conclusions were reached, the presence of a statistically significant effect between credit risk indicators and financial soundness indicators, with the exception of the loan-to-assets ratio on the profitability index, because the level of significance (9.5%) is higher than the acceptable level (5%).